A Survey on Antimicrobial Sensitivity Pattern of Different Antibiotics on Clinical Isolates of Pseudomonas aeruginosa Collected from Dhaka City of Bangladesh - Shahriar, M.; Akter, S. (Journal of Scientific Research, 2010)
A study of antimicrobial sensitivity of Pseudomonas aeruginosa isolated from clinical sources from different diagnostic centers, Dhaka, Bangladesh was carried out to facilitate the preference of drug in the management of Pseudomonas aeruginosa induced symptoms. Very low sensitivity of P. aeruginosa towards co-trimoxazole (45%), azithromycin (30%) and erythromycin (35%) was observed. Higher sensitivity pattern was observed for cefuroxime (57.5%). and only imipenem (100%) has shown sensitivity pattern possibly susceptible enough to consider for the management of P. aeruginosa induced cases in the area under study. The low sensitivity to different antimicrobial could be attributed to their prevailing usage and abuse in the area under study. Keywords: Antimicrobial sensitivity; Clinical isolates; Pseudomonas aeruginosa. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.6014 J. Sci. Res. 3 (1), 187-189 (2011)